Effects of vildagliptin relative to sulfonylureas in Muslim patients with type 2 diabetes fasting during Ramadan: influence of age and treatment with/without metformin in the VIRTUE study - Hassoun, Ahmed AK (Diabetes Metab Syndr Obes, 2016)
BACKGROUND: VIRTUE was a prospective, observational study assessing the effectiveness and safety of vildagliptin vs sulfonylureas (SUs) (both as monotherapy and in combination with metformin) in patients with type 2 diabetes mellitus who fasted during Ramadan. A post hoc analysis was carried out to assess the effect of treatment with/without metformin and age (<65 years or ≥65 years). PATIENTS AND METHODS: Patients were recruited from the Middle East and Asia. The primary end point was proportion of patients with one or more hypoglycemic event (HE) during Ramadan. Secondary end points included change from baseline in glycated hemoglobin (HbA1c), body weight, and safety. RESULTS: Overall, 684 patients received vildagliptin and 631 received SUs. Most patients received dual therapy with metformin (n=1,148) and were aged <65 years (n=1,189). A few patients experienced one or more HE with vildagliptin vs SU monotherapy (6.5% vs 14.5%) and with vildagliptin + metformin vs SUs + metformin (5.3% vs 20.6%); the latter achieved statistical significance (P<0.001) in both age subgroups (<65 years: 5.5% vs 18.4%, P<0.001; ≥65 years: 2.8% vs 30.9%, P<0.001). Vildagliptin was associated with numerically greater HbA1c and body weight reductions vs SUs, regardless of the therapy type or age. A higher proportion of SU- vs vildagliptin-treated patients experienced adverse events across all subgroups. CONCLUSION: A few patients experienced HEs with vildagliptin vs SUs regardless of age, and in patients on dual therapy. Vildagliptin ± metformin was also associated with good glycemic and weight control and was well tolerated. Vildagliptin might be a useful treatment option for patients with type 2 diabetes mellitus, particularly high-risk populations such as the elderly fasting during Ramadan.